Digital parenting burdens in China: Online homework, parent chats and punch-in culture - LIM, Sun Sun (Institutional Knowledge at Singapore Management University, 2024)
Presenting the first English language book on this topic, authors Sun Sun Lim and Yang Wang offer valuable insights into understanding how family life around is shifting in the face of digitalisation not only in China, but globally.